High-safety nickel cobalt lithium manganate semi-solid battery and preparation method thereof
By adopting gradient doping and heterogeneous cladding technology in the positive electrode material of nickel-cobalt-manganate semi-solid state batteries, and combining the dual-gradient functional layer composite separator design, the battery's challenges in the stability, interface contact, energy density and safety of the positive electrode material, and achieving high-safety batteries with high energy density and long cycle life.
Patent Information
- Application Number
- CN202510353443.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-25
AI Technical Summary
Existing semisolid lithium-ion batteries have challenges in the stability of the positive electrode material, interface contact, energy density and safety, resulting in insufficient cycling performance and safety.
The positive electrode triple composite modification strategy is adopted to optimize the positive electrode structure of nickel-cobalt-manganese oxide and the double-gradient functional layer composite separator design through element gradient doping, heterogeneous cladding layer pre-dumbling with solid electrolyte, and improve the coordinated optimization of body-interface-ion transmission of the positive electrode material.
Semi-solid state batteries with high safety, high energy density (>360Wh/kg) and long cycle life are achieved, which significantly improves the cycle stability and safety of the battery.
Smart Images

Figure CN119864515A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, in particular to a high-safety lithium nickel cobalt manganese oxide semi-solid battery and a preparation method thereof. Background Art
[0002] With the rapid development of electric vehicles and energy storage systems, higher requirements are placed on the energy density, safety and cycle life of batteries. Traditional liquid lithium batteries are flammable and have the risk of thermal runaway, and their cycle life is limited. Although all-solid-state batteries are highly safe, they have large solid-solid contact interface impedance and low ionic conductivity. Due to technical complexity and cost issues, they have not yet been commercialized on a large scale. Semi-solid-state batteries, as a transitional solution, reduce the proportion of liquid electrolytes and introduce solid electrolytes, which combine the high ionic conductivity of liquid electrolytes (ionic conductivity>1×10 -3 S / cm) and the high mechanical stability of solid electrolytes, it has the advantages of high safety and long cycle life.
[0003] At present, semi-solid-state batteries have attracted widespread attention from industry, academia and research circles. However, the following problems still exist in the existing technology: (1) Poor stability of positive electrode materials: Commonly used nickel cobalt manganese oxide (NCM) positive electrode materials have a high voltage platform and specific capacity, and can provide high energy density. However, as the Ni content increases, the highly reactive Ni formed in the later stage of material charging 4+ It will cause the stability of the positive electrode / electrolyte interface to decrease, leading to the oxidation and decomposition of the electrolyte. At the same time, the structural, chemical and mechanical stability of the material itself will gradually deteriorate, and the cycle performance will decay rapidly, which will seriously limit its safe industrial application. In addition, due to the mixing of lithium and nickel and the residual lithium on the surface of the material, the chemical and electrochemical stability of the positive electrode material will deteriorate, and the particles will crack, which will lead to the deterioration of the battery cycle stability; (2) Poor interface contact: The solid-solid contact between the solid electrolyte and the positive electrode particles has high interface impedance, which affects the ion transfer efficiency; (3) Energy density bottleneck: The energy density of traditional semi-solid batteries is generally lower than 350 Wh / kg, which is difficult to meet the needs of high-end applications; (4) Poor battery safety: It is difficult to ensure the high safety of the battery while ensuring the electrochemical performance of the battery.
[0004] The prior art attempts to improve the interface stability of the ternary positive electrode by optimizing the structure of the positive electrode material. Chinese patent CN119170763A Disclosed is a lithium nickel manganese oxide positive electrode material and a preparation method and application thereof. The positive electrode is modified by a coral-like coating layer (the coating layer material includes Al, Ti, and Zr). Although the dissolution of transition metals is suppressed, the ion transmission path of the positive electrode interface is not optimized; U.S. Patent US20220173101A1 discloses a fin field effect transistor with a merged drift region, which optimizes the electrode structure by a gradient compaction process, but does not involve chemical modification of the material, and does not solve the positive electrode interface problem from the material itself; Chinese patent CN113745455A discloses a ternary positive electrode sheet for lithium batteries and a preparation method and use thereof. The main method is to add an oxide solid electrolyte of a specific particle size to the positive electrode sheet. Although the method can improve the high safety of the battery, the added oxide electrolyte is easy to agglomerate during the ball milling process, and the prepared battery is equivalent to the existing liquid battery (260-300Wh / kg), the energy density is low, and the advantages of semi-solid batteries are not reflected, and it is difficult to meet the requirements of high energy density of batteries in fields such as drones; Chinese patent CN 118752738A discloses a solid electrolyte membrane and a lithium-ion battery, wherein the solid electrolyte membrane comprises a base membrane and a coating coated on at least one surface of the base membrane, wherein the coating comprises a solid electrolyte layer, wherein the solid electrolyte is reduced during formation to generate a uniform and dense interphase layer, thereby avoiding internal short circuit caused by direct contact between the aluminum current collector and the negative electrode, and can pass a heavy object impact test of the battery in a fully charged state. Although the electrolyte membrane improves the safety performance of the battery, the cycle and rate performance of the battery are poor.
[0005] In summary, existing improvement schemes (such as single element doping and single oxide coating) can only partially improve the above problems, and the process is complex and the cost is high. Summary of the invention
[0006] In order to solve the above problems, the purpose of the present invention is to provide a highly safe nickel cobalt manganese oxide lithium semi-solid state battery and a method for preparing the same. The present invention proposes a three-step composite modification strategy for the positive electrode, and realizes the coordinated optimization of the bulk-interface-ion transport of the positive electrode material through element gradient doping, heterogeneous coating layer and solid electrolyte pre-blending. Based on this, the present invention can obtain a semi-solid state battery with high safety, high energy density (>360Wh / kg) and long cycle life by optimizing the positive electrode structure of nickel cobalt manganese oxide lithium and the design of a dual gradient functional layer composite diaphragm.
[0007] The invention provides a highly safe nickel-cobalt-manganese-oxide lithium semi-solid battery, comprising a positive electrode, a negative electrode, a double-gradient functional layer composite diaphragm and a highly safe electrolyte.
[0008] The positive electrode comprises a positive electrode current collector and a modified lithium nickel cobalt manganese oxide positive electrode material arranged on the surface of the positive electrode current collector.
[0009] Furthermore, the modified nickel cobalt manganese oxide positive electrode material includes a modified nickel cobalt manganese oxide active material, a positive electrode conductor, a positive electrode binder and an inorganic solid electrolyte.
[0010] Furthermore, when preparing the modified lithium nickel cobalt manganese oxide positive electrode material, the inorganic solid electrolyte is prepared into a slurry as one of the raw materials, wherein the inorganic solid electrolyte is prepared into a slurry, specifically, the inorganic solid electrolyte powder is mixed with a solvent; Furthermore, the chemical formula of the modified lithium nickel cobalt manganese oxide active material is LiNi x Co y Mn 1-x-y O2, wherein 0≤x≤1, and the active material comprises a core body and a shell layer, the core body is a NCM core body doped with Ti and F gradient, and the shell layer is Li2TiO3 / LiAl X B 1-x O2 composite double-layer coating structure; Furthermore, the core body is a gradient doped NCM core, wherein Ti 4+ The doping concentration gradient is formed from the center (concentration of 0.5 at%) to the surface (concentration of 1.5 at%), F - A doping concentration gradient is formed from the center (concentration of 2at%) to the surface (concentration of 1at%), in which Ti occupies the transition metal position with a doping concentration of 0.5-1.5at%, and F partially replaces the O position to inhibit lattice oxygen loss with a doping concentration of 1-2at%.
[0011] Furthermore, the shell layer is a composite double-layer coating structure, wherein the inner layer is 0.5-2 nm thick Li2TiO3 (lithium ion conductor) and the outer layer is 1-3 nm thick LiAl 0.7 B 0.3 O2 glass phase (combining lithium ion conductivity and mechanical toughness).
[0012] Furthermore, the positive electrode conductive agent includes one or more of conductive carbon black (Super P), multi-walled carbon nanotubes (SWCNT), vapor grown carbon fiber (VGCF) and graphene.
[0013] Furthermore, the positive electrode binder includes one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), and polytetrafluoroethylene (PTFE).
[0014] Furthermore, the solvent includes one or more of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), and acetonitrile (ACN).
[0015] Furthermore, the inorganic solid electrolyte is one or more of a NASICON structure electrolyte, a LISICON structure electrolyte, a thio-LISICON structure electrolyte, a perovskite-type electrolyte, a garnet structure oxide electrolyte, a sulfide electrolyte and a halide electrolyte.
[0016] Furthermore, the NASICON structure electrolyte includes one of LATP and LAGP, the garnet structure oxide electrolyte includes one of LLZO and LLZTO, the perovskite electrolyte includes LLTO, and the sulfide electrolyte includes Li7P3S 7.5 O 3.5 , Li6PS5Cl, and the halide electrolyte includes one of Li3InCl6, Li3InBr6, and Li3InI6.
[0017] Furthermore, the particle size D50 of the inorganic solid electrolyte particles is 5nm~90nm.
[0018] Furthermore, the mass ratio of the modified lithium nickel cobalt manganese oxide active material, the inorganic solid electrolyte, the positive electrode conductor, and the positive electrode binder is (85~98): (0.5~10): (0.5~5): (0.5~5).
[0019] Furthermore, the modified lithium nickel cobalt manganese oxide active material is a high-nickel NCM positive electrode, including one or more of NCM8 series and NCM9 series active materials.
[0020] Furthermore, among the modified nickel cobalt manganese oxide active materials, NCM8 series active materials include NCM811; and NCM9 series active materials include NCM90.
[0021] The dual-gradient functional layer composite diaphragm provided by the present invention is a sandwich dual-gradient structure, including a base layer in the middle, a negative electrode side gradient layer and a positive electrode side gradient layer respectively attached to the two side surfaces of the base layer.
[0022] Furthermore, the base layer of the dual gradient functional layer composite diaphragm is: a polyarylethersulfone (PAES) porous membrane is used as a substrate, the polyarylethersulfone (PAES) porous membrane has a thickness of 5-10μm, a porosity of 60-75%, a decomposition temperature>450°C, and a tensile strength of ≥200Mpa, and has both high temperature resistance and resistance to dendrite puncture.
[0023] Furthermore, the negative electrode side gradient layer of the dual gradient functional layer composite diaphragm is an in-situ grown titanium nitride / polyvinylidene fluoride (TiN@PVDF) mixed coating with a thickness of 2-3 μm, wherein TiN is a nanowire with a diameter of 10-50 nm and is vertically arranged to form an ion fast channel, while PVDF provides a flexible buffer layer to reduce interface stress.
[0024] Furthermore, the negative electrode side gradient layer of the dual gradient functional layer composite diaphragm was prepared by the following method: TiN nanowire powder and PVDF (Mw = 1,000,000) were mixed in a mass ratio of 7:3, and then NMP was added to adjust the solid content to 25wt%, and then carbon nanotubes (CNT) were added to make the mass fraction of CNT 0.2wt%, CNT was used as a conductive agent, and then ball milled at a speed of 300rpm for 4 hours. The viscosity of the slurry obtained after ball milling reached 4500±2 00mPa·s, and then the magnetic field-assisted scraping method is used to coat the above slurry on the negative electrode side of the PAES base membrane, and the obtained wet film thickness is 30μm. Immediately afterwards, a vertical magnetic field with a strength of 0.5T is applied to align the TiN nanowires along the direction of the magnetic field, and then preheated at 80℃ for 1 minute, and then transferred to a 120℃ vacuum oven for curing for 2 hours to form an oriented porous layer with a thickness of 2.5μm, and the surface resistance of the oriented porous layer is <10Ω / sq. The above-mentioned oriented porous layer is the negative electrode side gradient layer.
[0025] Furthermore, the positive electrode side gradient layer of the dual gradient functional layer composite diaphragm is a porous polyvinyl alcohol (PVA) coating with a thickness of 1-2 μm loaded with solid electrolyte, and the mass fraction of the solid electrolyte increases from 30% to 60% from the inside (close to the PAES base membrane) to the outside (contacting the positive electrode), thereby achieving synergistic optimization of ion conduction and oxidation resistance.
[0026] Further, the solid electrolyte includes at least one of a sulfide solid electrolyte, a garnet solid electrolyte, a LISICON solid electrolyte, a NASICON solid electrolyte, a perovskite solid electrolyte, and an inorganic halide electrolyte; Furthermore, the solid electrolyte is selected from Li 1+x Al x Ti 2-x (PO4)3(0.1 <x<0.6)、Li 3x La (2 / 3)-x TiO3(0.04 <x<0.15)、Li7La3M2O 12 (M is one or more of Zr, Ta, Nb), Li 7-m PS 6-m X n(X=Cl, Br, I; 0≤m≤2), xLi2S(100-x) P2S5(50<x≤75), Li7P3S 7.5 O 3.5 , Li 1.5 Al 0.5 Ge 1.5 (PO4)3(LAGP), Li3MX6(M=trivalent metal; X=Cl, Br and I), Li x+5 Ln3Z y A z O 12 (A is at least one element selected from Al, Ga, Sc, Yb, Dy, Ta, Ti, V, Y, Nb, hf, Si, Ge, Sn, 1.4≤x≤2, 0<y<2.0, 0<z<2.0) one or more selected from; wherein the particle size D50 of the solid electrolyte particles is 10nm-200nm; Furthermore, in the solid electrolyte, the NASICON type solid electrolyte includes one of LATP and LAGP, and the garnet type solid electrolyte includes LLZO (Li7La3Zr2O 12 )、LLZTO(Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 ), the perovskite solid electrolyte includes LLTO (Li 0.33 La 0.56 TiO3), sulfide solid electrolytes including Li7P3S 7.5 O 3.5 , one of Li6PS5Cl, and the inorganic halide electrolyte includes one of Li3InCl6, Li3InBr6, and Li3InI6.
[0027] Furthermore, the positive electrode side gradient layer of the dual gradient functional layer composite diaphragm is prepared by the following method: First, the modified LATP electrolyte powder was prepared: LATP solid electrolyte powder with a particle size of 100 nm and silane coupling agent (KH-550) were dispersed in ethanol at a mass ratio of 1:0.02, dried at 60°C and set aside; then, the inner layer, middle layer and outer layer slurries were prepared respectively: the inner layer slurry (i.e., the positive electrode side contacting the PAES base membrane) used 70g of 5wt% polyvinyl alcohol (PVA) aqueous solution as the matrix, added 30g of modified LATP electrolyte powder and 0.1g of polyacrylic acid (PAA) dispersant, and the viscosity after ball milling was controlled to 2500mPa·s; the middle layer slurry used 70g of 5wt% PVA aqueous solution, added 45g of modified LATP electrolyte powder and 0.05g of PAA, and the viscosity after ball milling was controlled to 2100mPa·s; the outer layer slurry used 70g of 5wt% PVA aqueous solution, added 60g of modified LATP electrolyte powder, the viscosity after ball milling is controlled to be 1800mPa·s; then the inner layer slurry, the middle layer slurry and the outer layer slurry are coated in sequence: the inner layer slurry (wet film thickness 15μm) is first scraped on the positive electrode side of the PAES base membrane, and immediately pre-cured for 20 seconds with 3W / cm² infrared radiation (wavelength 3-5μm) to form a semi-dry base layer; then the middle layer slurry (wet film thickness 15μm) is superimposed and coated, and immediately pre-cured for 20 seconds with 3W / cm² infrared radiation (wavelength 3-5μm); finally, the outer layer slurry (wet film thickness 15μm) is coated, and immediately pre-cured for 20 seconds with 3W / cm² infrared radiation (wavelength 3-5μm) to form a dense surface layer with a high LATP content, which is then dried in a hot air cycle at 80°C for 4 hours to obtain a composite coating with a total thickness of 1.8μm and a LATP content continuously increasing from 30% to 60%. The online optical monitoring of the interlayer thickness deviation is <5%, that is, the positive electrode side gradient layer is obtained.
[0028] Furthermore, the negative electrode comprises a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, and the negative electrode active material layer comprises a negative electrode active material, a negative electrode conductive agent and a negative electrode binder; Furthermore, the negative electrode satisfies the following conditions: (1) The negative electrode active material includes one or more of graphite, hard carbon, silicon-carbon composite material, and silicon-oxygen composite material; (2) The negative electrode conductive agent includes one or more of conductive carbon black (Super P, i.e. SP), multi-walled carbon nanotubes (SWCNT), carbon fiber and graphene; (3) The negative electrode binder includes one or more of polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and polyacrylic acid (PAA); (4) The mass ratio of the negative electrode active material, the negative electrode conductive agent and the negative electrode binder is (93-98.5): (1.0-3.0): (0.5-4.0); (5) The negative electrode current collector is copper foil or carbon-coated copper foil; Furthermore, the high-safety electrolyte includes an electrolyte solvent and a solute; Further, the electrolyte solvent in the high-safety electrolyte includes one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and ethylene carbonate (EC); Furthermore, the solute in the high-safety electrolyte includes a lithium salt and an additive, the lithium salt includes one or more of LiPF6, LiDFOB, LiBF4, LiTFSI, LiBOB, and LiFSI, and the additive includes one or more of a film-forming additive, a flame retardant additive, an overcharge additive, and a high temperature or low temperature additive; Further, the film-forming additive includes one or more of vinylene carbonate (VC), propylene carbonate (PC) and fluoroethylene carbonate (FEC); Further, the flame retardant additive includes one or more of trimethyl phosphate (TMP), ethyl hexafluorophosphate (FEP) and propyl pentafluorophosphate (FPP); The present invention also provides a method for preparing the above-mentioned high-safety nickel cobalt lithium manganese oxide semi-solid battery, which is specifically as follows: The positive electrode, negative electrode, dual-gradient functional layer composite membrane and high-safety electrolyte are prepared respectively, and then the positive electrode, dual-gradient functional layer composite membrane and negative electrode are placed in sequence and then wound, and then packaged with aluminum-plastic film, baked to remove moisture, and then injected with the high-safety electrolyte, left to stand at room temperature, formed, aged, and then divided to obtain the semi-solid-state battery.
[0029] The semi-solid-state battery is a nickel-cobalt-manganese-oxide lithium semi-solid-state battery with high energy density, long cycle and high safety.
[0030] In the semi-solid battery provided by the present invention, the modified nickel cobalt manganese oxide positive electrode material can not only improve the structural stability and interface stability of the positive electrode material, but also expand the lithium ion transmission channel and improve the interface ion and electron transmission rate; in the semi-solid battery provided by the present invention, the double gradient functional layer composite diaphragm can improve the ion mobility between the positive and negative electrodes and the diaphragm interface, improve the interface stability, and achieve safe dynamic protection of the battery. The semi-solid battery assembled by using the positive electrode material of the above-mentioned semi-solid battery to prepare the positive electrode sheet, the negative electrode sheet prepared by the negative electrode material and the double gradient functional layer composite diaphragm, and the high-safety electrolyte has high cycle stability and high safety.
[0031] Compared with the prior art, the present invention has the following beneficial effects: (1) The modified positive electrode active material used in the present invention can achieve the synergistic effect of gradient doping + double coating: wherein Ti 4+ Stable layered structure, F − Reduce oxygen activity; Li2TiO3 increases Li + Diffusion rate, LiAl x B 1-x O2 glass inhibits electrolyte corrosion; it is prepared using low-temperature atomic layer deposition (ALD) technology: it can avoid material decomposition caused by traditional high-temperature coating treatment; (2) During the battery cycle, the lithium in the positive electrode is extracted and embedded in the negative electrode to form a SEI film, causing irreversible loss of lithium, resulting in reduced battery capacity and initial efficiency. When the nickel content in the modified nickel cobalt manganese oxide positive electrode material is high, the lithium-nickel mixing and oxygen loss in the positive electrode cause the positive electrode structure stability to deteriorate. The mixed solid electrolyte can provide lithium ions to re-lithiate the charged nickel cobalt manganese oxide positive electrode, reduce the charge state of the positive electrode, delay its structural decomposition and oxygen release at high temperature, and improve the thermal stability of the material and the safety of the battery. (3) The dual-gradient functional layer composite diaphragm used in the present invention has high ionic conductivity (>1.5mS / cm): the metal-like electronic conductivity of TiN can assist the desolvation of lithium ions, and the solid electrolyte in the gradient layer on the positive electrode side can provide a three-dimensional lithium ion migration network. The composite conductivity is 300% higher than that of the traditional PE diaphragm. In addition, the electrode / diaphragm interface impedance control can be achieved: the TiN array on the negative electrode side can reduce the disordered growth of the SEI film, and the solid electrolyte in the gradient layer on the positive electrode side can inhibit the oxidative decomposition of the electrolyte on the positive electrode side. Finally, the dual-gradient functional layer composite diaphragm used in the present invention can provide dynamic safety protection: the pore shrinkage rate of the PAES substrate at 150°C is <5% (better than 80% of traditional PE / PP), combined with the flame retardant properties of the solid electrolyte, it will not burn or explode in a 187°C hot box test, which can significantly improve the safety of the battery; (4) The high energy density, long cycle and high safety nickel cobalt manganese oxide semi-solid state battery provided by the present invention uses the modified nickel cobalt manganese oxide positive electrode material, double gradient functional layer composite diaphragm and electrolyte of the above nickel cobalt manganese oxide semi-solid state battery. During 2040 cycles, the battery capacity retention rate is always maintained above 80%, and it does not catch fire or explode when punctured. The thermal runaway temperature is increased to 187°C, and it has good cycle stability and high safety. (5) The present invention provides a method for preparing a nickel cobalt manganese oxide lithium semi-solid state battery, which has a simple process, is compatible with existing equipment, has low energy consumption, is environmentally friendly, and has low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1is a SEM image of the gradient precursor obtained in step a of step (1) in Example 1; Figure 2 is a SEM image of the gradient core-shell structure precursor obtained in step c of step (1) in Example 1; Figure 3 is a SEM image of a cross section of a dual gradient functional layer composite diaphragm in Example 3; Figure 4 1 is a comparison diagram of the impedance of the semi-solid batteries prepared in Example 3 and Comparative Example 2 after the first cycle; Figure 5 1 is a comparison diagram of the first effects of the semi-solid batteries prepared in Example 3 and Comparative Example 2; Figure 6 It is a comparison chart of the cycle performance of the semi-solid batteries prepared in Example 3 and Comparative Example 2 at room temperature 25°C and 0.33C rate conditions; Figure 7 is a comparison chart of the capacity retention rates of the semi-solid batteries prepared in Example 3 and Comparative Example 2 respectively after being stored at 55° C. for 7 days; Figure 8 3 is a comparison diagram of the thermal runaway critical temperatures of the semi-solid batteries prepared in Example 3 and Comparative Example 2; Fig. 9 This is a comparison chart of the gas production of the batteries of Example 3 and Comparative Example 2 when stored at 70°C for 7 days. DETAILED DESCRIPTION
[0033] In order to better understand the content of the present invention, the present invention will be further described below in conjunction with specific embodiments and drawings. The following embodiments are implemented based on the technology of the present invention, and detailed implementation methods and operating steps are given, but the protection scope of the present invention is not limited to the following embodiments.
[0034] Embodiment 1: (1) Modified lithium nickel cobalt manganese oxide (LiNi 0.8 Mn 0.1 Co 0.1 O2, namely NCM811) active material preparation, through dynamic co-precipitation + gradient doping sintering process to achieve Ti 4+ Forming a doping concentration gradient from the center (concentration of about 0.5at%) to the surface (concentration of about 1.5at%), F - A doping concentration gradient is formed from the center (concentration is about 1at%) to the surface (concentration is about 2at%), and Li2TiO3 / LiAl is formed on the surface of Ti / F gradient-doped NCM811 core by low-temperature ALD deposition process. x B 1−x O2 composite coating layer. The specific preparation process is as follows: a. Core preparation: Microfluidic co-precipitation technology was used to prepare high F (2.0 at%) and low Ti (0.5 at%) doped Ni 0.8 Mn 0.1 Co 0.10 Precursor, firstly, NiSO4·6H2O, MnSO4·H2O, and CoSO4·7H2O are dissolved in deionized water and mixed evenly to obtain a main salt solution a, wherein the concentration of NiSO4·6H2O is 0.8M, the concentration of MnSO4·H2O is 0.1M, and the concentration of CoSO4·7H2O is 0.1M; tetrabutyl titanate (TBOT) and citric acid are added into deionized water and stirred thoroughly to obtain a citric acid chelate solution a containing TBOT, wherein the concentration of TBOT is 0.05M, and the molar ratio of TBOT to citric acid is 1:3; NH4F is added into deionized water and mixed evenly to obtain an NH4F solution a, wherein the concentration of NH4F is 0.2M; then the main salt solution a, the citric acid chelate solution a containing tetrabutyl titanate, and the NH4F solution a are simultaneously pumped into the reactor, wherein the flow rate of the main salt solution a is 10mL / min, and the flow rate of the citric acid chelate solution a containing TBOT is 0.5 mL / min, the flow rate of NH4F solution a was 2.0 mL / min, and NaOH / NH3 composite precipitant was injected into the reactor at a flow rate of 8 mL / min. The co-precipitation reaction was carried out at 55°C and a stirring speed of 800 rpm, wherein the NaOH / NH3 composite precipitant was a solution of pH = 11.0 prepared by adding NaOH and NH3 to deionized water; maintaining a high alkaline environment to promote rapid nucleation, Ti 4+ Due to the delayed release of chelation, it is evenly incorporated into the body phase. - It preferentially adsorbs on the surface of the particles to form a highly doped area; the coprecipitation reaction lasts for 40 minutes from the beginning of adding each reactant, and the mixed solution obtained by the reaction is centrifuged at 3000 rpm to collect the precipitate, and washed three times with an ethanol-water mixture (the volume ratio of ethanol to deionized water in the mixture is 3:1) to remove free ions, and finally vacuum dried at 60°C for 12 hours to obtain a gradient precursor with a particle size D50 of 120 nm, a surface F content of approximately 2.0 at%, and a bulk Ti content of approximately 0.5 at%.
[0035] b. Preparation of intermediate transition layer: The gradient precursor obtained in step a is used as the matrix, and a dynamic linear adjustment process is used to achieve continuous change of Ti / F in the transition zone of the matrix surface: NiSO4·6H2O, MnSO4·H2O, and CoSO4·7H2O are dissolved in deionized water and mixed evenly to obtain a main salt solution b, wherein the concentration of NiSO4·6H2O is 8M, the concentration of MnSO4·H2O is 1.0M, and the concentration of CoSO4·7H2O is 1.0M. Tetrabutyl titanate (TBOT) and citric acid are added to deionized water. After sufficient stirring, a citric acid chelating solution b containing TBOT is obtained, wherein the concentration of TBOT is 0.10M and the molar ratio of TBOT to citric acid is 1:3. NH4F is added to deionized water and mixed evenly to obtain NH4F solution b, wherein the concentration of NH4F is 0.15M; then the main salt solution b, the citric acid chelating solution b containing TBOT and the NH4F solution b are synchronously pumped into the reactor, wherein the flow rate of the main salt solution b is 10mL / min, the flow rate of the citric acid chelating solution b containing TBOT is 1.0 mL / min, and the flow rate of the NH4F solution b is 1.5mL / min (that is, relative to step a, the concentration of the citric acid chelating solution containing TBOT is increased from 0.05M to 0.10M, corresponding to Ti doping 0.5→1.0at%, and its flow rate is linearly increased from 0.5mL / min to 1.0mL / min, with a gradient slope of 0.017mL / min 2 ; The concentration of NH4F solution decreased from 0.2M to 0.15M, corresponding to F 2.0→1.5at%, and the flow rate decreased from 2.0mL / min to 1.5mL / min, with a slope of 0.017mL / min 2 ); At the same time, NaOH / NH3 composite precipitant was injected into the reactor at a flow rate of 6 mL / min, wherein the NaOH / NH3 composite precipitant was a solution of pH = 10.0 prepared by adding NaOH and NH3 into deionized water, and the temperature was set to 60 ° C. The laminar shear effect of the microfluidic reaction chamber was used to guide the Ti 4+ Preferentially doped into the granular epitaxial layer, F - Due to NH4 + The adsorption amount decreased with decreasing concentration. After 60 minutes of reaction, the mixed solution obtained by the reaction was collected by centrifugation and washed three times with anhydrous ethanol to obtain a transition layer precursor with a continuous Ti / F gradient (Ti 0.5 (pointing to the center) → 1.0 at%, F 2.0 (pointing to the center) → 1.5 at%) and a particle size D50 of 160 nm.
[0036] c. Preparation of surface layer: Using the transition layer precursor obtained in step b as the matrix, a surface layer structure is formed on its surface: NiSO4·6H2O, MnSO4·H2O, and CoSO4·7H2O are dissolved in deionized water and mixed evenly to obtain a main salt solution c, wherein the concentration of NiSO4·6H2O is 8M, the concentration of MnSO4·H2O is 1.0M, and the concentration of CoSO4·7H2O is 1.0M. Tetrabutyl titanate (TBOT) and citric acid are added to deionized water and stirred thoroughly. After stirring, a citric acid chelating solution c containing TBOT was obtained, wherein the concentration of TBOT was 0.15 M, and the molar ratio of TBOT to citric acid was 1:3. NH4F was added to deionized water and mixed evenly to obtain an NH4F solution c, wherein the concentration of NH4F was 0.10 M. Then, the main salt solution c, the citric acid chelating solution c containing TBOT, and the NH4F solution c were simultaneously pumped into the reactor, wherein the flow rate of the main salt solution c was 10 mL / min, and the flow rate of the citric acid chelating solution c containing TBOT was 1.5 mL / min, the flow rate of NH4F solution c is 1.0 mL / min (that is, relative to step b, the concentration of the citric acid chelating solution containing TBOT is increased from 0.10 M to 0.15 M, corresponding to Ti doping 1.0→1.5 at%, and its flow rate is 1.5 mL / min; the concentration of NH4F solution is reduced from 0.15 M to 0.10 M, corresponding to F 1.5→1.0 at%, and the flow rate is 1.0 mL / min), and at the same time, the composite precipitant c is injected into the reactor at a flow rate of 4 mL / min. The composite precipitant c is a mixed solution prepared by mixing 0.2 M NaOH aqueous solution and 0.05 M NH3 aqueous solution, and the pH is stabilized at 9.5. The composite precipitant c also adds polyacrylic acid (PAA) dispersant to inhibit particle agglomeration, wherein the mass ratio of PAA to the mass of the mixed solution with a pH of 9.5 is 0.1 wt%; the reactor is kept at 65 ° C and stirred at a high intensity of 1000 rpm (shear rate> 500 s -1 ) Enhance mass transfer and promote Ti + The citric acid preferentially occupies the octahedral lattice sites on the particle surface through the citric acid chelation-dissociation mechanism. - The competitive adsorption of PAA reduces the surface residue; after the reaction, the mixture is centrifuged at 4000 rpm for 10 minutes, washed three times with an ethanol-acetone mixture (the volume ratio of ethanol to acetone is 3:1) to remove free Ti / F ions, and then freeze-dried (specifically pre-frozen at -50°C for 4 hours and vacuum dried for 12 hours) to fix the surface components, and finally annealed at 300°C for 30 minutes in an Ar / 5% CF4 atmosphere to compensate for the surface F loss to 0.8 at%, forming a gradient core-shell structure precursor with a particle size D50 of 200 nm, a surface Ti content of approximately 1.5 at%, and a F content of approximately 0.8 at%.
[0037] d. High-temperature lithiation and gradient doping locking Lithium mixing and pre-calcination: The core-shell structure precursor obtained in the above step c is mixed with LiOH•H2O at a molar ratio of Li / (Ni+Mn+Co)=1.05 (where Ni:Mn:Co=8:1:1), and then pre-calcined at 450°C for 4h in an oxygen atmosphere to form a Li2O intermediate phase, promote the solid solution of Ti / F elements in the lattice, and obtain a pre-calcined product.
[0038] Gradient sintering process: First, the product obtained after the above pre-sintering was heated from room temperature to 800℃ and kept at this temperature for 6h for crystallization. During the sintering, oxygen was introduced with an oxygen flow rate of 2 L / min and a heating rate of 5℃ / min to make Ti 4+ Occupies Ni site (the central Ti-rich region inhibits Li / Ni mixing), F - Partially replace the O position (the low F area on the surface retains oxygen activity), and then anneal at low temperature 500℃ for 2h. During the annealing, Ar gas containing 5% CF4 is introduced to compensate the surface F content using F free radicals generated by CF4 decomposition, forming a concentration gradient from the center (F concentration is about 2 at%) to the surface (F concentration is about 1 at%); promote the diffusion of Ti / F elements along the grain boundaries, lock the gradient distribution, and finally obtain Ti / F gradient-doped NMC811 particles; e. Using the above Ti / F gradient doped NMC811 particles as the matrix, a low temperature atomic layer deposition (ALD) method is used to form Li2TiO3 / LiAl on its surface. x B 1-x O2 composite coating: First, the precursor tetrakis(dimethylamino)titanium (TDMAT) and ozone were alternately pulsed deposited under nitrogen protection, and 50 cycles were completed at 100°C (one cycle means that TDMAT pulse deposition was used first, and then ozone pulse deposition was used) to form an amorphous TiO2 layer with a thickness of 1.5 nm. Subsequently, lithium tert-butoxide (LiOtBu) vapor was introduced at 120°C for in-situ lithiation reaction to generate an ion conductor Li2TiO3 inner layer with a thickness of about 2 nm; then the precursor was switched to trimethylaluminum and triethylborane (the mass ratio of the two was 1:1), and water vapor and ozone were alternately pulsed for 15 cycles (one cycle means that water vapor pulse deposition was used first, and then ozone pulse deposition was used) to deposit an Al2O3 / B2O3 composite layer with a thickness of about 2.5 nm. Finally, LiOtBu vapor was introduced at 80°C for lithiation of the Al2O3 / B2O3 composite layer, and it was converted into a LiAl2TiO3 composite layer with a thickness of about 3 nm after nitrogen annealing at 150°C for 1 hour. 0.7 B 0.3 The outer layer of O2 glass phase eventually forms a continuous and dense Li2TiO3 / LiAlBO double-layer heterogeneous coating structure. The interlayer interface achieves atomic-level matching through the ALD self-limiting reaction, and finally obtains the modified nickel cobalt manganese oxide active material.
[0039] (2) Preparation of modified nickel cobalt manganese oxide positive electrode sheet: First, weigh 2.5 kg of the modified nickel cobalt manganese oxide active material in step (1) and add it to a slurry mixing kettle, then add 0.028 kg of polyvinylidene fluoride (PVDF) binder and stir evenly, then add 0.3 kg of lithium aluminum titanium phosphate (LATP) electrolyte slurry with a solid content of 15% and stir evenly, wherein the LATP electrolyte slurry is obtained by mixing LATP powder with a particle size of 50 nm and NMP in a mass ratio of 16:84, then add 0.04 kg of conductive carbon black to the slurry mixing kettle and stir evenly, then add 0.8 kg of NMP to the slurry mixing kettle, adjust the slurry viscosity to 3600 mPa•s, and finally obtain a modified nickel cobalt manganese oxide positive electrode slurry with a solid content of 72%; then apply the slurry on aluminum foil and dry to obtain a positive electrode roll; the surface density of the unrolled positive electrode sheet is 340 g / m 2 , roller compaction density is 3.2g / cm 3 , cut into 80mm wide pole rolls, 100m dressing length, and then cut into positive pole sheets with length and width of 70mm×80mm respectively; (3) Preparation of negative electrode sheets: First, 1.0 kg of graphite and 0.17 kg of silicon-carbon composite material were stirred and evenly mixed. Then, 0.024 kg of Spuer P conductive agent and 1.0 kg of deionized water were added and stirred and dispersed respectively. Then, 0.05 kg of CMC slurry with a solid content of 20%, 0.05 kg of SBR slurry with a solid content of 20%, and 0.1 kg of PAA slurry with a solid content of 20% were added and stirred respectively (the above CMC slurry, SBR slurry, and PAA slurry are obtained by mixing CMC, SBR, and PAA with deionized water, respectively). According to the viscosity of the slurry, 0.8 kg of deionized water was added to adjust the slurry viscosity to 3600 / mpas, and finally a negative electrode slurry with a solid content of 54% was obtained.
[0040] The negative electrode is coated by a coating machine, and the copper foil is used as the negative electrode current collector. The above negative electrode slurry is coated on the copper foil, dried in an oven, and wound to obtain a negative electrode roll. The density of the negative electrode sheet before rolling is 160g / m 2 Then it is rolled by a roller press, and the roller compaction density is set to 1.6g / cm 3 , cut into pole rolls with a width of 82mm and a length of 100m, and then cut into negative pole sheets with a length and width of 72mm×82mm respectively.
[0041] (4) Preparation of dual gradient functional layer composite membrane: f. Preparation of base layer (PAES porous membrane): First, 0.12 kg of polyarylethersulfone (PAES, Mw=50,000-80,000) was dissolved in 0.88 kg of N-methylpyrrolidone (NMP), and the concentration of the solution obtained after stirring was 12 wt %. Then, 0.053 kg of polyethylene glycol (PEG-4000) was added as a pore-forming agent, so that the mass fraction of PEG-4000 was 0.5 wt %. Then, magnetic stirring was performed at 60 ° C for 6 h to completely dissolve, and vacuum degassing was performed for 30 minutes. Then, The vacuum degassing solution was uniformly coated on the PET release film by slit extrusion method, with an initial wet film thickness of 200 μm, and then entered the first stage of gradient humidity coagulation bath, specifically, stayed at 25°C and 70% humidity for 30 seconds to initially form surface micropores, followed by the second stage, specifically, stayed at 50°C and 40% humidity for 2 minutes to induce internal through-hole structure, and finally, washed with water to remove residual solvent, and vacuum dried at 60°C for 6 hours to obtain a PAES base film with a porosity of 65±3% and a thickness of 8 μm; g. Preparation of negative electrode side gradient layer (TiN@PVDF vertical array coating): Preparation of TiN nanowires: First, using copper foil as a substrate, TiCl4 as a titanium source, NH3 as a nitrogen source, and Ar / H2 mixed gas (wherein the volume ratio of Ar to H2 is 9:1) as a carrier, TiN nanowires are synthesized by chemical vapor deposition (CVD) method, and the reaction temperature is set to 800°C. The obtained nanowires are peeled off to obtain TiN nanowire powder (the diameter of the TiN nanowires in the powder is 50±5nm and the length is 3-5μm). Then 0.7kg of the above TiN nanowire powder is mixed with PVDF (Mw=1,000,000) at a mass ratio of 7:3, and then NMP is added to adjust the solid content to 25wt%, and then carbon nanotubes (CNTs) are added to make the mass fraction of CNTs 0.2wt%, CNTs are used as conductive agents, and then ball milled at a speed of 300rpm for 4 hours, and the slurry viscosity reaches 4500±200mPa·s.
[0042] Vertical array coating: The slurry was coated on the negative electrode side of the PAES base membrane by magnetic field-assisted scraping. The obtained wet film thickness was 30 μm. A vertical magnetic field with a strength of 0.5 T was immediately applied to align the TiN nanowires along the magnetic field direction. The film was then preheated at 80°C for 1 minute and then transferred to a 120°C vacuum oven for curing for 2 hours to form an oriented porous layer with a thickness of 2.5 μm. The surface resistance of the oriented porous layer was <10 Ω / sq.
[0043] h. Preparation of positive electrode side gradient layer (LATP@PVA gradient coating): First, the modified LATP electrolyte powder was prepared: the LATP solid electrolyte powder with a particle size of 100 nm and the silane coupling agent (KH-550) were dispersed in ethanol at a mass ratio of 1:0.02, dried at 60 °C and set aside. Then, the inner layer, middle layer and outer layer three-layer LATP@PVA slurry were prepared respectively: the inner layer slurry (i.e., the positive electrode side contacting the PAES base film) used 70g of polyvinyl alcohol (PVA) aqueous solution with a mass fraction of 5wt% as the matrix, and 30g of the modified The slurry was made of 70g of 5wt% PVA aqueous solution, 45g of modified LATP electrolyte powder and 0.05g of PAA, and the viscosity was controlled to 2100mPa·s after ball milling; the outer layer slurry was made of 70g of 5wt% PVA aqueous solution, 60g of modified LATP electrolyte powder (without dispersant) was added, and the viscosity was controlled to 2500mPa·s after ball milling. agent), the viscosity after ball milling was controlled to 1800mPa·s to promote dense stacking; then a multi-channel slit coater was used to sequentially coat the inner layer slurry, the middle layer slurry, and the outer layer slurry: the inner layer slurry (wet film thickness 15μm) was first scraped on the positive electrode side of the PAES base film, and immediately pre-cured for 20 seconds with 3W / cm² infrared radiation (wavelength 3-5μm) to form a semi-dry base layer; then the middle layer slurry (wet film thickness 15μm) was superimposed and immediately irradiated with 3W / cm² infrared radiation (wavelength 3-5μ m) pre-curing for 20 seconds to ensure no mixing between layers; finally, apply the outer layer slurry (wet film thickness 15μm), immediately pre-curing with 3W / cm² infrared radiation (wavelength 3-5μm) for 20 seconds to form a dense surface layer with high LATP content, and then dry in a hot air cycle at 80℃ for 4 hours to obtain a composite coating with a total thickness of 1.8μm and a LATP content continuously increasing from 30% to 60%. The online optical monitoring of the interlayer thickness deviation is less than 5%, achieving the synergistic optimization of ion conduction and antioxidant properties.
[0044] (5) Electrolyte preparation: Ethyl methyl carbonate (EMC), diethyl carbonate (DEC) and propylene carbonate (PC) were mixed at a mass ratio of 3:1:1 to prepare 84.5 g of a non-aqueous organic solvent. Then, 0.2 g of propane sultone (PS) and 0.3 g of methylene disulfonate (MMDS) were added to the non-aqueous organic solvent as additives. Then, 0.5 g of fluoroethylene carbonate (FEC) and 0.5 g of diethylene sulfate (DTD) as negative electrode film-forming agents were added and mixed to obtain a solution that was the electrolyte.
[0045] (6) Cell assembly: 20 positive electrode sheets prepared in step (2), 21 negative electrode sheets prepared in step (3) and the dual gradient functional layer composite diaphragm prepared in step (4) are stacked to form a 10Ah soft-pack cell (wherein the positive electrode sheet and the negative electrode sheet are respectively located on both sides of the dual gradient functional layer composite diaphragm), then the tabs are welded, the aluminum-plastic film is encapsulated, and the cell is baked at 55°C for 48 hours. The electrolyte prepared in step (5) is injected, the clamp pressure is 4 N•m, and the cell is left standing at room temperature for 24 hours, followed by formation, aging, and then capacity division to obtain a highly safe nickel cobalt manganese oxide lithium semi-solid state battery.
[0046] Embodiment 2: (1) Modified lithium nickel cobalt manganese oxide (LiNi 0.9 Mn 0.05 Co 0.05 Preparation of active materials of NCM90: According to the preparation method of step (1) in Example 1, the preparation of Ni doped with high F (2.0 at%) and low Ti (0.5 at%) in step a of Example 1 was carried out. 0.8 Mn 0.1 Co 0.10 Precursor" was replaced by "Preparation of high F (2.0 at%) and low Ti (0.5 at%) doped Ni 0.90 Mn 0.05 Co 0.05 Precursor", and the concentration of NiSO4·6H2O in the main salt solution a is replaced with 0.90M, the concentration of MnSO4·H2O is 0.05M, and the concentration of CoSO4·7H2O is 0.05M, and the rest is the same as in Example 1; (2) Preparation of positive electrode sheet: This step is the same as in Example 1; according to the preparation method of step (2) in Example 1, the LATP electrolyte in Example 1 is replaced by LAGP, and the NCM811 is replaced by NCM90, and the rest is the same as in Example 1; (3) Preparation of negative electrode sheet: This step is the same as in Example 1; (4) Preparation of a dual-gradient functional layer composite membrane: According to the preparation method of step (4) in Example 1, the LATP electrolyte in Example 1 is replaced by LAGP, and the rest is the same as in Example 1; (5) Electrolyte preparation: This step is the same as in Example 1; (6) Cell assembly: This step is the same as in Example 1.
[0047] Embodiment 3: (1) Modified lithium nickel cobalt manganese oxide (LiNi 0.9 Mn 0.05 Co 0.05 O2, i.e. NCM90) active material preparation: This step is the same as in Example 2; (2) Preparation of positive electrode sheet: According to the preparation method of step (2) in Example 2, the LAGP electrolyte in Example 2 is replaced by LLZTO (Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 ), the rest is the same as in Example 2; (3) Preparation of negative electrode sheet: This step is the same as in Example 1; (4) Preparation of a dual-gradient functional layer composite membrane: According to the preparation method of step (4) in Example 1, the LATP electrolyte in Example 1 is replaced by LLZTO, and the rest is the same as Example 1; (5) Electrolyte preparation: This step is the same as in Example 1; (6) Cell assembly: This step is the same as in Example 1.
[0048] Embodiment 4: (1) Modified lithium nickel cobalt manganese oxide (LiNi 0.9 Mn 0.05 Co 0.05 Preparation of O2, i.e. NCM90) active material: This step is the same as in Example 2; (2) Preparation of positive electrode sheet: According to the preparation method of step (2) in Example 2, the LAGP electrolyte in Example 2 is replaced by LLTO (Li 0.33 La 0.56 TiO3), the rest is the same as in Example 2; (3) Preparation of negative electrode sheet: This step is the same as in Example 1; (4) Preparation of a dual-gradient functional layer composite membrane: According to the preparation method of step (4) in Example 1, the LATP electrolyte in Example 1 is replaced by LLTO, and the rest is the same as in Example 1; (5) Electrolyte preparation: This step is the same as in Example 1; (6) Cell assembly: This step is the same as in Example 1.
[0049] Embodiment 5: (1) Modified lithium nickel cobalt manganese oxide (LiNi 0.9 Mn 0.05 Co 0.05 Preparation of O2, i.e. NCM90) active material: This step is the same as in Example 2; (2) Preparation of positive electrode sheet: According to the preparation method of step (2) in Example 2, the LAGP electrolyte in Example 2 is replaced by LLZO (Li7La3Zr2O 12 ), the rest is the same as in Example 2; (3) Preparation of negative electrode sheet: This step is the same as in Example 1; (4) Preparation of a dual-gradient functional layer composite membrane: According to the preparation method of step (4) in Example 1, the LATP electrolyte in Example 1 is replaced by LLZO, and the rest is the same as Example 1; (5) Electrolyte preparation: This step is the same as in Example 1; (6) Cell assembly: This step is the same as in Example 1.
[0050] Embodiment 6: (1) Modified lithium nickel cobalt manganese oxide (LiNi 0.9 Mn 0.05 Co 0.05 Preparation of O2, i.e. NCM90) active material: This step is the same as in Example 2; (2) Preparation of positive electrode sheet: According to the preparation method of step (2) in Example 2, the LAGP electrolyte in Example 2 is replaced by Li7P3S 7.5 O 3.5 , the rest is the same as in Example 2; (3) Preparation of negative electrode sheet: This step is the same as in Example 1; (4) Preparation of dual gradient functional layer composite membrane: According to the preparation method of step (4) in Example 1, the LATP electrolyte in Example 1 is replaced by Li7P3S 7.5 O 3.5 , the rest is the same as in Example 1; (5) Electrolyte preparation: This step is the same as in Example 1; (6) Cell assembly: This step is the same as in Example 1.
[0051] Embodiment 7: (1) Modified lithium nickel cobalt manganese oxide (LiNi 0.9 Mn 0.05 Co 0.05 Preparation of O2, i.e. NCM90) active material: This step is the same as in Example 2; (2) Preparation of positive electrode sheet: According to the preparation method of step (2) in Example 2, the LAGP electrolyte in Example 2 is replaced by Li6PS5Cl, and the rest is the same as Example 2; (3) Preparation of negative electrode sheet: This step is the same as in Example 1; (4) Preparation of a dual-gradient functional layer composite membrane: According to the preparation method of step (4) in Example 1, the LATP electrolyte in Example 1 is replaced by Li6PS5Cl, and the rest is the same as in Example 1; (5) Electrolyte preparation: This step is the same as in Example 1; (6) Cell assembly: This step is the same as in Example 1.
[0052] Comparative Example 1: (1) Preparation of positive electrode slurry: Select undoped high nickel NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O2) as the positive electrode active material: weigh 2.5 kg of positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O2 was added to the slurry kettle, and then 0.028 kg of binder PVDF was added and mixed. After stirring evenly, 0.04 kg of conductive carbon black was added to make slurry. The stirrer revolution speed was set to 80 rpm and the dispersion speed was set to 1000 rpm. After stirring evenly, 0.5 kg of NMP was added and the slurry viscosity was adjusted to 3600 mPa•s. Finally, a high nickel 8 series (LiNi) with a solid content of 72% was obtained. 0.8 Co 0.1 Mn 0.1 O2) positive electrode slurry.
[0053] (2) Preparation of positive electrode sheet: This step is the same as in Example 1; (3) Preparation of negative electrode sheet: This step is the same as in Example 1; (4) Preparation of common electrolyte membrane: a. Add 0.3kg of Al2O3 particles with a particle size D50 of 50nm to 0.5kg of NMP and stir evenly to obtain a slurry, and add the dispersant PVA, surfactant CTAB and binder PVDF-HFP to the above slurry in the mass ratio of Al2O3:PVA:PVDF-HFP:CTAB=96%:2.5%:1%:0.5% in sequence, and mix evenly; prepare Al2O3 coating slurry, the Al2O3 coating slurry has a solid content of 36.9% and a viscosity of 100 mPa•s. Apply the Al2O3 coating slurry to one side of a 9μm thick PE base film by a coating machine, and after drying the slurry, obtain a base film with a 3μm thick Al2O3 layer coated on one surface; b. Dissolve 0.2 kg PVDF-HFP in 0.8 kg NMP, stir to form a uniform colloidal slurry, apply the obtained colloidal slurry on the other side of the base film, obtain a PVDF-HFP coating of about 2 μm thickness, and finally obtain a common electrolyte diaphragm. Cut the obtained diaphragm into 86 mm width for standby use.
[0054] (5) Electrolyte preparation: This step is the same as in Example 1; (6) Cell assembly: This step is the same as in Example 1.
[0055] Comparative Example 2: (1) Preparation of positive electrode slurry: Weigh 2.5 kg of positive electrode material LiNi 0.9 Co 0.05Mn 0.05 O2 (NCM90) was added to the slurry kettle, and then 0.028 kg of binder PVDF was added and mixed, and stirred evenly, wherein the stirrer revolution speed was set to 100 rpm, and then 0.04 kg of graphene was added for slurry preparation, and the stirrer revolution speed was set to 80 rpm, and the dispersion speed was set to 1000 rpm, and stirred evenly, and then 0.5 kg of NMP was added, and the slurry viscosity was adjusted to 3300 mPa•s, and finally a high nickel 9 series (LiNi) with a solid content of 69% was obtained. 0.9 Co 0.05 Mn 0.05 O2) cathode slurry; (2) Preparation of positive electrode sheet: This step is the same as in Example 1; (3) Preparation of negative electrode sheet: This step is the same as in Example 1; (4) Preparation of common electrolyte membrane: This step is the same as that of Comparative Example 1; (5) Electrolyte preparation: This step is the same as in Example 1; (6) Cell assembly: This step is the same as in Example 1.
[0056] Figure 1 This is the SEM image of the gradient precursor obtained in step a of step (1) in Example 1. The measured values of the core diameter of the gradient precursor are shown in Table 1.
[0057] Table 1
[0058] Figure 2 This is a SEM image of the gradient core-shell structure precursor obtained in step (1) c in Example 1. The diameter measurement values of the gradient core-shell structure precursor are shown in Table 2.
[0059] Table 2
[0060] Figure 3 This is a SEM image of the cross-section of the dual-gradient functional layer composite diaphragm in Example 3; after testing, the ionic conductivity of the diaphragm is 1.8mS / cm: the metal-like electronic conductivity of TiN assists lithium ion desolvation, and the LLZTO electrolyte provides a three-dimensional lithium ion migration network, and the composite conductivity is 300% higher than that of the traditional PE diaphragm. The electrode / diaphragm interface impedance is 1.5Ω·cm², in which the TiN array on the negative electrode side can reduce the disordered growth of the SEI film, and the gradient LLZTO electrolyte on the positive electrode side inhibits the oxidation and decomposition of the positive electrode electrolyte. In terms of dynamic safety protection: the pore shrinkage rate of the PAES substrate at 150°C is <5% (better than 80% of traditional PE / PP), combined with the flame retardant properties of the LLZTO electrolyte, it will not explode after a 185°C hot box test.
[0061] Figure 4 is a comparison diagram of the impedance of the batteries prepared in Example 3 and Comparative Example 2 after the first cycle; Figure 4 It can be seen that the impedance of Example 3 is significantly smaller than that of Comparative Example 2, indicating that the modified nickel cobalt manganese oxide lithium positive electrode material and the double gradient functional layer composite diaphragm can significantly reduce the interfacial impedance of the battery.
[0062] Figure 5 is a comparison chart of the first effects of the batteries prepared in Example 3 and Comparative Example 2; Figure 5 It can be seen that the first-cycle coulombic efficiency of the semi-solid battery of Example 3, i.e., the use of modified nickel cobalt manganese oxide lithium positive electrode material and double gradient functional layer composite diaphragm, is 99.8%, which is significantly higher than that of Comparative Example 2, i.e., the unmodified nickel cobalt manganese oxide lithium positive electrode material and ordinary diaphragm battery (96.5%).
[0063] Figure 6 is a comparison chart of the cycle performance of the batteries prepared in Example 3 and Comparative Example 2 at room temperature 25°C and 0.33C rate conditions, Figure 6 It can be seen that after 2040 cycles, the capacity retention rate of Example 3 is 80%, while the capacity of Comparative Example 2 decays rapidly after 500 cycles, and the capacity retention rate has decayed to 80% after 960 cycles. The results show that the modified nickel cobalt manganese oxide lithium positive electrode material and the dual gradient functional layer composite diaphragm can significantly improve the battery cycle stability.
[0064] Figure 7 is a comparison chart of the capacity retention rate of the batteries prepared in Example 3 and Comparative Example 2 after being stored at 55° C. for 7 days; Figure 7 It can be seen that the capacity retention rate of the semi-solid battery prepared in Example 3 after storage at 55°C for 7 days is 96.5%, which is significantly higher than that of Comparative Example 2, indicating that the modified nickel cobalt manganese oxide lithium positive electrode material and the dual gradient functional layer composite diaphragm can significantly improve the high temperature storage performance of the battery.
[0065] Figure 8 is a comparison diagram of thermal runaway temperatures of batteries prepared in Example 3 and Comparative Example 2; Figure 8 It can be seen that the thermal runaway temperature of Example 3 is 187°C, and the thermal runaway temperature of Comparative Example 2 is 131°C. Example 3 is significantly higher than Comparative Example 2, indicating that the modified nickel cobalt manganese oxide lithium positive electrode material and the dual gradient functional layer composite diaphragm can significantly improve the thermal stability of the battery.
[0066] Fig. 9 The comparison chart of gas production of the two batteries of Example 3 and Comparative Example 2 stored at 70°C for 7 days; Fig. 9It can be seen that the gas production of Example 3 is 0.4 mL, while the gas production of Comparative Example 2 is 4.6 mL. Example 3 is significantly smaller than Comparative Example 2, indicating that the modified nickel cobalt manganese oxide lithium positive electrode material and the dual gradient functional layer composite diaphragm can significantly reduce the side reactions inside the battery.
[0067] Table 3 Comparison of the performance of the electrolyte membranes prepared in Example 3 and Comparative Example 2
[0068] It can be seen from Table 3 that the ionic conductivity of the separator of Example 3 is 1.8 mS / cm, which is significantly higher than that of Comparative Example 2. The thermal stability and mechanical strength of the separator of Example 3 are better than those of Comparative Example 2, indicating that the electrolyte-coated separator has excellent puncture strength, tensile strength and thermal shrinkage, which can improve the battery puncture and thermal safety.
[0069] The semi-solid batteries prepared by assembling the battery cells of Examples 1-7 and the batteries prepared by assembling the battery cells of Comparative Examples 1-2 were subjected to relevant electrical and other performance tests, and the results are shown in Table 4.
[0070] Table 4
[0071] It can be seen from Table 4 that the DCR of Examples 1-7 after constant capacity is lower than that of Comparative Examples 1 and 2, the capacities are higher than those of Comparative Examples 1 and 2, the boundary heating temperatures are higher than those of Comparative Examples 1 and 2, and the batteries of Examples 1-7 can pass the needle puncture after being fully charged, while Comparative Examples 1 and 2 fail to pass. After 2000 cycles, the capacity retention rates of the batteries are also higher than those of Comparative Examples 1 and 2. The results show that the modified nickel cobalt manganese oxide lithium positive electrode material and the dual gradient functional layer composite diaphragm can not only reduce the battery impedance and improve the battery capacity retention rate, but also significantly improve the battery needle puncture and thermal safety.
[0072] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A highly safe nickel-cobalt-manganese-oxide lithium semi-solid battery, characterized in that: It includes positive electrode, negative electrode, double gradient functional layer composite diaphragm and high safety electrolyte; The positive electrode comprises a positive electrode current collector and a modified lithium nickel cobalt manganese oxide positive electrode material disposed on the surface of the positive electrode current collector; The modified nickel cobalt lithium manganese oxide positive electrode material comprises a modified nickel cobalt lithium manganese oxide active material, a positive electrode conductor, a positive electrode binder and an inorganic solid electrolyte; The chemical formula of the modified lithium nickel cobalt manganese oxide active material is LiNi x Co y Mn 1-x-y O2, wherein 0≤x≤1, and the active material comprises a core body and a shell layer, the core body is a NCM core body doped with Ti and F gradient, and the shell layer is Li2TiO3 / LiAl X B 1-x O2 composite double-layer coating structure; The core body is a gradient doped NCM core with Ti 4+ Forming a doping concentration gradient from the center to the surface, F - A doping concentration gradient is formed from the center to the surface, wherein Ti occupies the transition metal position, the doping concentration is 0.5-1.5at%, and the concentration at the center is 0.5at%, and the concentration at the surface is 1.5at%; F partially replaces the O position to inhibit the loss of lattice oxygen, the doping concentration is 1-2at%, and the concentration at the center is 2at%, and the concentration at the surface is 1at%; the shell layer is a composite double-layer coating structure, wherein the inner layer is a 0.5-2nm thick Li2TiO3 ion conductor, and the outer layer is a 1-3nm thick LiAl 0.7 B 0.3 O2 glass phase; The dual-gradient functional layer composite diaphragm is a sandwich dual-gradient structure, including a base layer in the middle, and a negative electrode side gradient layer and a positive electrode side gradient layer respectively attached to the two side surfaces of the base layer.
2. The highly safe nickel-cobalt-manganese-oxide lithium semi-solid battery according to claim 1, characterized in that: The mass ratio of the modified lithium nickel cobalt manganese oxide active material, inorganic solid electrolyte, positive electrode conductor and positive electrode binder is (85~98): (0.5~10): (0.5~5): (0.5~5); the positive electrode conductor includes one or more of conductive carbon black, multi-walled carbon nanotubes, vapor-grown carbon fibers and graphene; the positive electrode binder includes one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene and polytetrafluoroethylene; the particle size D50 of the inorganic solid electrolyte particles is 5nm~90nm, and the inorganic solid electrolyte is one or more of a NASICON structure electrolyte, a LISICON structure electrolyte, a thio-LISICON structure electrolyte, a perovskite electrolyte, a garnet structure oxide electrolyte, a sulfide electrolyte and a halide electrolyte; the modified lithium nickel cobalt manganese oxide active material is a high-nickel NCM positive electrode, including one or more of NCM8 series and NCM9 series active materials.
3. The highly safe nickel-cobalt-manganese-oxide lithium semi-solid battery according to claim 2, characterized in that: Among the modified nickel cobalt manganese oxide active materials, the NCM8 series active materials include NCM811; the NCM9 series active materials include NCM90; the NASICON structure electrolyte includes one of LATP and LAGP, the garnet structure oxide electrolyte includes one of LLZO and LLZTO, the perovskite electrolyte includes LLTO, and the sulfide electrolyte includes Li7P3S 7.5 O 3.5 , Li6PS5Cl, and the halide electrolyte includes one of Li3InCl6, Li3InBr6, and Li3InI6.
4. The highly safe nickel-cobalt-manganese-oxide lithium semi-solid battery according to claim 1, characterized in that: The base layer of the dual gradient functional layer composite diaphragm is: a polyarylethersulfone porous membrane is used as a substrate, the polyarylethersulfone porous membrane has a thickness of 5-10μm, a porosity of 60-75%, a decomposition temperature>450°C, and a tensile strength of ≥200Mpa; the negative electrode side gradient layer is an in-situ grown titanium nitride / polyvinylidene fluoride mixed coating, the thickness of the mixed coating is 2-3μm, wherein TiN is a nanowire with a diameter of 10-50nm and is vertically arranged to form an ion fast channel; the positive electrode side gradient layer is a porous polyvinyl alcohol coating with a thickness of 1-2μm loaded with a solid electrolyte, and the mass fraction of the solid electrolyte increases from 30% to 60% from the inside to the outside; the solid electrolyte includes at least one of a sulfide solid electrolyte, a garnet solid electrolyte, a LISICON solid electrolyte, a NASICON solid electrolyte, a perovskite solid electrolyte, and an inorganic halide electrolyte.
5. The highly safe nickel-cobalt-manganese-oxide lithium semi-solid battery according to claim 4, characterized in that: The solid electrolyte is selected from Li 1+x Al x Ti 2-x (PO4)3(0.1 <x<0.6)、Li 3x La (2 / 3)-x TiO3(0.04 <x<0.15)、Li7La3M2O 12 (M is one or more of Zr, Ta, Nb), Li 7-m PS 6-m X n (X=Cl, Br, I; 0≤m≤2), xLi2S(100-x) P2S5 (50<x≤75), Li7P3S 7.5 O 3.5 , Li 1.5 Al 0.5 Ge 1.5 (PO4)3, Li3MX6 (M = trivalent metal; X = Cl, Br and I), Li x+5 LqCy y A z O 12 (A is at least one element selected from Al, Ga, Sc, Yb, Dy, Ta, Ti, V, Y, Nb, hf, Si, Ge, Sn, 1.4≤x≤2, 0<y<2.0, 0<z<2.0) one or more selected from; wherein the particle size D50 of the solid electrolyte particles is 10nm-200nm; Among the solid electrolytes, the NASICON type solid electrolyte includes one of LATP and LAGP, the garnet type solid electrolyte includes one of LLZO and LLZTO, the perovskite type solid electrolyte includes LLTO, and the sulfide solid electrolyte includes Li7P3S 7.5 O 3.5 , one of Li6PS5Cl, and the inorganic halide electrolyte includes one of Li3InCl6, Li3InBr6, and Li3InI6.
6. The highly safe nickel-cobalt-manganese-oxide lithium semi-solid battery according to claim 4, characterized in that: The negative electrode side gradient layer of the dual gradient functional layer composite diaphragm is prepared by the following method: TiN nanowire powder and PVDF are mixed in a mass ratio of 7:3, wherein the Mw of PVDF is 1,000,000, and then NMP is added to adjust the solid content to 25wt%, and then CNT is added to make the mass fraction of CNT 0.2wt%, and then ball milled at a speed of 300rpm for 4 hours. The viscosity of the slurry obtained after ball milling reaches 4500±200mPa·s, and then the magnetic field assisted scraping method is used to apply the above slurry on the negative electrode side of the PAES base membrane. The obtained wet film thickness is 30μm, and then a vertical magnetic field with a strength of 0.5T is immediately applied, and then preheated at 80℃ for 1 minute, and then transferred to a 120℃ vacuum oven for curing for 2 hours to form a directional porous layer with a thickness of 2.5μm, and the surface resistance of the directional porous layer is <10Ω / sq. The above directional porous layer is the negative electrode side gradient layer.
7. The highly safe nickel-cobalt-manganese-oxide lithium semi-solid battery according to claim 4, characterized in that: The positive electrode side gradient layer of the dual gradient functional layer composite diaphragm is prepared by the following method: First, the modified LATP electrolyte powder was prepared: LATP solid electrolyte powder with a particle size of 100 nm and silane coupling agent KH-550 were dispersed in ethanol at a mass ratio of 1:0.02, dried at 60°C and set aside; then, the inner layer, middle layer and outer layer slurries were prepared respectively: the inner layer slurry, i.e., the positive electrode side contacting the PAES base membrane, used 70g of a polyvinyl alcohol aqueous solution with a mass fraction of 5wt% as the matrix, added 30g of the modified LATP electrolyte powder and 0.1g of a polyacrylic acid dispersant, and the viscosity was controlled to be 2500mPa·s after ball milling; the middle layer slurry used 70g of a PVA aqueous solution with a mass fraction of 5wt%, added 45g of the modified LATP electrolyte powder and 0.05g of PAA, and the viscosity was controlled to be 2100mPa·s after ball milling; the outer layer slurry used 70g of a PVA aqueous solution with a mass fraction of 5wt%, added 60g of the modified LATP electrolyte powder, and ball milled The viscosity is controlled at 1800mPa·s; then the inner layer slurry, the middle layer slurry and the outer layer slurry are applied in sequence: the inner layer slurry is first applied on the positive side of the PAES base film, the inner layer slurry has a wet film thickness of 15μm, and it is immediately pre-cured with infrared radiation at 3W / cm² and a wavelength of 3-5μm for 20 seconds to form a semi-dry base layer; then the middle layer slurry is superimposed and applied, the wet film thickness of the middle layer slurry is 15μm, and it is immediately pre-cured with infrared radiation at 3W / cm² and a wavelength of 3-5μm for 20 seconds Pre-curing for 20 seconds; finally, apply the outer layer slurry with a wet film thickness of 15μm. Immediately pre-curing with infrared radiation at 3W / cm² and a wavelength of 3-5μm for 20 seconds forms a dense surface layer with a high LATP content. Then, dry it in a hot air cycle at 80℃ for 4 hours to obtain a composite coating with a total thickness of 1.8μm and a LATP content continuously increasing from 30% to 60%. The online optical monitoring of the interlayer thickness deviation is less than 5%, that is, the positive side gradient layer is obtained.
8. The highly safe nickel-cobalt-manganese-oxide lithium semi-solid battery according to claim 1, characterized in that: The negative electrode comprises a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, a negative electrode conductive agent and a negative electrode binder; The negative electrode meets the following conditions: (1) The negative electrode active material includes one or more of graphite, hard carbon, silicon-carbon composite material, and silicon-oxygen composite material; (2) The negative electrode conductive agent includes one or more of conductive carbon black, multi-walled carbon nanotubes, carbon fibers and graphene; (3) The negative electrode binder includes one or more of polytetrafluoroethylene, carboxymethyl cellulose, styrene-butadiene rubber, and polyacrylic acid; (4) The mass ratio of the negative electrode active material, the negative electrode conductive agent and the negative electrode binder is (93-98.5): (1.0-3.0): (0.5-4.0); (5) The negative electrode current collector is copper foil or carbon-coated copper foil.
9. The highly safe nickel-cobalt-manganese-oxide lithium semi-solid battery according to claim 1, characterized in that: The high-safety electrolyte includes an electrolyte solvent and a solute, wherein the electrolyte solvent includes one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and vinyl carbonate; the solute includes a lithium salt and an additive, wherein the lithium salt includes one or more of LiPF6, LiDFOB, LiBF4, LiTFSI, LiBOB, and LiFSI, and the additive includes one or more of a film-forming additive, a flame retardant additive, an overcharge additive, and a high temperature or low temperature additive; the film-forming additive includes one or more of vinylene carbonate, propylene carbonate and fluoroethylene carbonate; the flame retardant additive includes one or more of trimethyl phosphate, ethyl hexafluorophosphate and propyl pentafluorophosphate.
10. A method for preparing a highly safe nickel-cobalt-manganese-oxide lithium semi-solid battery according to any one of claims 1 to 9, characterized in that: The positive electrode, negative electrode, dual-gradient functional layer composite membrane and high-safety electrolyte are prepared respectively, and then the positive electrode, dual-gradient functional layer composite membrane and negative electrode are placed in sequence and then wound, and then packaged with aluminum-plastic film, baked to remove moisture, and then injected with the high-safety electrolyte, left to stand at room temperature, formed, aged, and then divided to obtain the semi-solid-state battery.
Citation Information
Patent Citations
Anode material for lithium ion battery and preparation method thereof
CN102354748A
Lithium air or oxygen battery
CN102593556A
Polyimide lithium ion battery diaphragm and battery using same
CN106784544A
Core-shell structure high nickel gradient nickel cobalt manganese aluminum quaternary positive electrode material and preparation method thereof
CN110518219A
Gradient doped lithium-rich manganese-based layered material with high inside and low outside and preparation method of gradient doped lithium-rich manganese-based layered material
CN114649526A
Cited By
Positive pole piece comprising lithium ion battery and power utilization device
CN121149156A
Gradient composite pole piece, preparation method and secondary battery
CN121565788A
High-safety doped ternary system lithium ion battery cell and preparation method thereof
CN121601741A